School-based Prevention of Commercial Sexual Exploitation: A Special Focus on the Needs of and Effective Services for At-Risk Urban African American Girls - Harper, Erin (2013)
The commercial sexual exploitation of children (CSEC) is a form of childhood sexual abuse that involves sexual exploitation for financial or economic gain. Low-income African American girls in urban settings are at high risk of CSEC and other stressors that increase risk of mental health problems that may interfere with academic functioning, school climate, and school safety. The twofold purpose of this qualitative research was to propose an evidence-based framework for school-based prevention of CSEC and to explore school-based mental health providers’ perceptions of low-income urban African American girls’ needs, as well as their perceptions and experiences related to girls’ resources and services that may increase girls’ protective factors and resiliency. The sample included seven females who each self-identified as middle to upper middle class African Americans with 11 years to 22 years of experience providing school-based mental health services to low-income urban African American youth. Each participant completed three in-depth interviews. Data were analyzed using an inductive-deductive model. Researchers attained 91% interrater agreement after coding three participants’ interviews and maintained an average of 90% interrater agreement. Two major themes emerged—Resilient Girls with Multiple Challenges and Contextually/Culturally Responsive Training and Service Provision. Participants were aware of numerous challenges to girls’ wellbeing and receipt of effective school-based mental health services and described girls as resilient in spite of these challenges. Participants did not perceive their practices as intentionally contextually/culturally responsive; however, they described some strategies that were consistent with existing research and professional standards related to contextually/culturally responsive service provision for African American, low-income, or urban youth. Participants reported that they often have insufficient time or resources to tailor services to address girls’ needs directly and that their services for girls are often one-time or discontinuous. Providers perceive a need for more collaboration, training, and school-wide initiatives to address girls’ context-specific needs. The results of this study support a need to enhance school-based mental health professionals’ understanding of low-income urban African American girls’ contextual challenges; a need to equip providers with strengths-based strategies for enhancing girls’ resiliency and resistance; and a need for providers to further examine their own biases